Understanding the formation of the Milky Way in the era of Gaia. Issue 67 (17th July 2015) - Minchev, I.; Chiappini, C.; Martig, M.
Abstract : The main goal of Galactic Archaeology is to understand the formation and evolution of the basic Galactic components. This requires sophisticated chemo-dynamical modeling, where disk asymmetries ( e.g., perturbations from the bar, spirals, and mergers) and non-equilibrium processes are taken into account self-consistently. Here we discuss the current status of Galactic chemo-dynamical modeling and focus on a recent hybrid technique, which helps circumvent traditional problems with chemical enrichment and star formation encountered in fully self-consistent cosmological simulations. We show that this model can account for a number of chemo-kinematic relations in the Milky Way, as discussed in previous works. In addition, we demonstrate that our model matches well the observed age-[α/Fe] relation and that blurring may be insufficient to explain the scatter in the age-metallicity relation.